Allegory and the poetic self : first-person narration in late medieval literature - Palmer, R. Barton, 1946-; Philipowski, Katharina-Silke; Rüthemann, Julia (University Press of Florida, 2022)
"This book examines the rise of an influential new family of poetry in the late Middle Ages, analyzing why the allegorical first-person romance embedded itself in the vernacular literature of Western Europe and remained popular for more than two centuries"--